Studi Komparatif Strategi Hilirisasi: Pembelajaran dari Model Tiongkok untuk Akselerasi Transformasi Ekonomi Indonesia Menuju Negara Maju - Syafa Maytara Sultri Mulza; Miftakhul Choiri (Jurnal Riset Akuntansi, 2026)
This study aims to analyze the structural, regulatory, institutional, and socio-ecological impacts of Indonesia and China's mineral downstreaming policies to formulate a framework for economic acceleration towards a developed economy. The qualitative research method employs a comparative case study of Indonesia's nickel downstreaming and China's strategic metals. Secondary data (2020–2025) are sourced from regulations, USGS reports, macroeconomic data, and academic literature collected through desk research. Data validity was tested using policy triangulation techniques. The analysis is dissected using the New Developmental State theory, which emphasizes active state intervention in synergizing policies, technological innovation, and global sustainability standards. The study results show a convergence between the two countries as architects of industrialization through defensive protectionism to compel investment. However, there is a divergence in the output structure: China has succeeded in leading the world in green technology through control of intellectual property, while Indonesia's downstreaming remains qualitatively fragile due to declining intersectoral linkages, shrinking local workforce, the impact of deforestation, and being trapped in the low-value upstream-midstream segment (refined dependency). To support the Golden Indonesia 2045 vision, Indonesia needs to selectively adopt the Chinese model through the implementation of a supply chain early warning system, adaptive fiscal incentives, core technology transfer via the Indonesia Battery Corporation (IBC), and the integration of Environmental, Social, and Governance (ESG) standards into industry governance.